Identify the Most Prominent Contemporary Atheistic Suspicions that Should Be Included in The Monotheism Curricula of Secondary Stage - Awad Al-Kahtany (Umm Al-Qura University, 2022)
This study aimed to identify the most prominent contemporary atheistic suspicions that should be included in the monotheism curricula of secondary stage, the degree to which they contain, and whether there are differences between the curriculums in their inclusion of those suspicions. To achieve the objectives of the study, content analysis was used, which is an approach of the descriptive method. The study tool was a content analysis card that included (15) contemporary atheistic suspicions. After confirming the validity and reliability of the tool, it was used to analyses the monotheism curricula of secondary stage (Ministry of Education edition 1443 / 2021). The study results illustrate that the monotheistic curriculum (1) for the secondary stage (course system) included the most prominent contemporary atheistic suspicions by (33.45%) and (96) frequencies. The monotheistic curriculum (2) for the secondary stage (course system) included the most prominent contemporary atheistic suspicions by (4.56) and (12) frequencies. the monotheistic curriculum (1) percentage of including most prominent contemporary atheistic suspicions was higher than the percentage of its inclusion in the monotheism curriculum (2). Based on the results of the study, it recommended that those who responsible for building and developing monotheism curricula for the secondary stage should refer to research, studies, and publications in contemporary atheism and benefit from them in reviewing and developing these curricula. It suggested that monotheism curricula of undergraduate students should be analyzed in the light of contemporary atheistic suspicions.